Synthesis and biological evaluation of novel indole-pyrazoline hybrid derivatives as potential topoisomerase 1 inhibitors. Issue 4 (15th February 2020) - Shu, Bing; Yu, Qian; Hu, De-xuan; Che, Tong; Zhang, Shang-shi; Li, Ding
Graphical abstract: Abstract: A series of novel indole-pyrazoline hybrid derivatives were designed, synthesized, and evaluated for topoisomerase 1 (Top1) inhibitory activity. Top1-mediated relaxation assays showed that our synthesized compounds had variable Top1 inhibitory activity. Among these compounds, 3-(5-(naphthalen-1-yl)-1-phenyl-4, 5-dihydro-1 H -pyrazol-3-yl)-1-(phenylsulfonyl)-1 H -indole (6n ) was found to be a strong Top1 inhibitor with better inhibitory activity than CPT and hit compounds. Our further experiments rationalized the mode of action for this new type of inhibitors, which showed no significant binding to supercoiled DNA.